Polyethylene Glycol Effect on the Transient and Steady State Phases of P-Nitrophenyltrimethyl Acetate Hydrolysis Catalyzed by ?-Chymotrypsin - Lissi-Gervaso, E; Calderon-Espinoza, C; Calderon-Espinoza, C (Sociedad Chilena de Quimica, 2013)
The effect of polyethylene glycol (PEG) on the hydrolytic activity of ?-chymotrypsin has been studied using p-nitrophenyltrimethyl acetate (PNTMA) as substrate. This substrate requires long times to reach the steady state condition, allowing the measurement by conventional methods of the fast initial "burst" step present on the biphasic catalytic behaviour exhibited by ?-chymotrypsin. The presence of PEG increases both the initial and steady state rates of the reaction. This increase was observed at all the substrate concentrations employed. A formal Michaelis-Menten treatment under steady state conditions shows that KM remains almost constant over the range of PEG concentrations studied (up to 20% w/v), whereas kcat moderately increases with the increment in PEG concentration. The results obtained in this work are interpreted in terms of the following mechanism:.
Keywords: Enzyme kinetics; chymotrypsin; p-nitrophenyl trimethylacetate; poly-ethyleneglycol